1988
DOI: 10.4315/0362-028x-51.12.976
|View full text |Cite
|
Sign up to set email alerts
|

The Shelf Life of Pasteurized Fresh Milk Manufactured in Saudi Arabia

Abstract: The keeping quality of pasteurized fresh milk was investigated. At 7°C storage, the product conformed to the Saudi Arabian Standard Organization for as long as 7 d and as short as 2 d with ≤10 cfu/ml coliform, ≤10 cfu/ml mold and yeast, ≤50,000 cfu/ml SPC and acceptable sensory qualities. Acceptable sensory attributes with coliform counts of <10 cfu/ml were maintained in the product for 10 d at 7°C. Molds, yeasts and psychrotrophs were instrumental in cutting down the shelf life of the product beyond 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The number of aerobic colonies in pasteurized milk varied between products A and B during the storage period, ranging between 3960-8680 cfu/ml in product A samples and between 15-48 cfu/ml for product B. Salji et al (1988) reported a similar result for the total count in pasteurised milk was 3200 cfu/ml after 10 days of storage at 7 °C. The low number of aerobics colonies in product B may be due to the pasteurization temperature of the milk, as it was pasteurized at 85 °C while product A was pasteurized at 78 °C.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The number of aerobic colonies in pasteurized milk varied between products A and B during the storage period, ranging between 3960-8680 cfu/ml in product A samples and between 15-48 cfu/ml for product B. Salji et al (1988) reported a similar result for the total count in pasteurised milk was 3200 cfu/ml after 10 days of storage at 7 °C. The low number of aerobics colonies in product B may be due to the pasteurization temperature of the milk, as it was pasteurized at 85 °C while product A was pasteurized at 78 °C.…”
Section: Resultsmentioning
confidence: 54%
“…This result is in line with the Saudi standard ( SASO 40:1990 ), as the standard required coliform bacteria in pasteurized milk should not exceed 10 cfu/ml of milk. Salji et al. (1988) reported a similar result with no change in the coliform count (<10 cfu/ml) during 10 days of storage of pasteurized milk at 7 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the heat treatment was effective and that there was no postpasteurization contamination. The presence of coliforms in pasteurized milk can be due to insufficient heat treatment (Raju and Nambutripad, 1987;Salji et al, 1988), or to contamination of a pasteurized product during packaging (Barnard, 1981;Burden et al, 1995).…”
Section: Coliform Countsmentioning
confidence: 99%
“…The presence of coliforms in pasteurised milk can be substantially originated from two events: an insufficient heat treatment, that frequently relies on a low microbiological quality of raw milk, principally in unfavourable geographical areas [16,17]; or a contamination of pasteurised product during packaging despite the surveillance programs of hygiene control throughout the process [1][2][3].…”
Section: Introductionmentioning
confidence: 99%